2021
DOI: 10.1016/j.apsb.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel PGAM5 inhibitor LFHP-1c protects blood–brain barrier integrity in ischemic stroke

Abstract: Blood–brain barrier (BBB) damage after ischemia significantly influences stroke outcome. Compound LFHP-1c was previously discovered with neuroprotective role in stroke model, but its mechanism of action on protection of BBB disruption after stroke remains unknown. Here, we show that LFHP-1c, as a direct PGAM5 inhibitor, prevented BBB disruption after transient middle cerebral artery occlusion (tMCAO) in rats. Mechanistically, LFHP-1c binding with endothelial PGAM5 not only inhibited the PGAM5 phosphatase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Deletion of PGAM5 has been shown to result in Parkinson’s-like movement disorder in mice (Lu et al, 2014) and T cell dysfunction in primary cells (Panda et al, 2016). While its diverse roles largely remain to be uncovered (Liang et al, 2021), a novel PGAM5 inhibitor was recently suggested as a potential therapeutic for brain ischemic stroke (Gao et al, 2021). We observed that PGAM5 displays elevated levels in the mitochondria isolated from brain, SKM and spleen, possibly explaining the tissue-specific phenotypes induced by its absence and where in the body molecules targeting its phosphatase activity would exert their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of PGAM5 has been shown to result in Parkinson’s-like movement disorder in mice (Lu et al, 2014) and T cell dysfunction in primary cells (Panda et al, 2016). While its diverse roles largely remain to be uncovered (Liang et al, 2021), a novel PGAM5 inhibitor was recently suggested as a potential therapeutic for brain ischemic stroke (Gao et al, 2021). We observed that PGAM5 displays elevated levels in the mitochondria isolated from brain, SKM and spleen, possibly explaining the tissue-specific phenotypes induced by its absence and where in the body molecules targeting its phosphatase activity would exert their effects.…”
Section: Discussionmentioning
confidence: 99%
“…It interacts with both NRF2 and KEAP1, linking them with mitochondria, with knockdowns of either PGAM5 or KEAP1, leading to an increase in the levels of NRF2, thus hinting at the repression of NRF2-dependent gene expression by PGAM5 [ 33 ]. There are cases in which inhibition of PGAM5 can be of therapeutic value, not only for cancer but also for other pathologies, through the use of LFHP-1c, a new PGAM5 inhibitor, which, in this case, allowed for enhanced activation of NRF2, with promising results for brain ischemic stroke by counteracting ischemia-induced Blood–Brain Barrier (BBB) disruption [ 111 ]. In another instance of a regulatory loop, NRF2 influences and is influenced by the levels of mitochondrial ROS.…”
Section: Part 2: Emerging Evidence Of the Interplay Between Nrf2 And ...mentioning
confidence: 99%
“…Moreover, LFHP-1c inhibited phosphatase activity of PGAM5 and reduced the interaction between PGAM5 and NRF2 in rat brain microvascular endothelial cells. LFHP-1c treatment increased pDRP1(Ser637), but whether LFHP-1c represses mitochondrial fission is unclear (Gao et al, 2021 ). Since the phosphatase activity of PGAM5 is required for its participation in mitochondrial fission, mitophagy and mitochondrial biogenesis (Wang et al, 2012 ; Chen et al, 2014 ; Bernkopf et al, 2018 ), LFHP-1c might open up a new therapeutic strategy to regulate mitochondrial homeostasis.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…While regulation of PGAM5-NRF2 mediated mitochondrial biogenesis in neurological diseases had not been previously reported, a recent study revealed that interaction between PGAM5 and NRF2 resulted in blood–brain barrier disruption and neurological deficits in ischemic stroke (Gao et al, 2021 ). Treatment of a novel inhibitor of PGAM5, LFHP-1c, inhibited phosphatase activity of PGAM5, disrupted PGAM5-NRF2 interaction, and thus allowed nuclear translocation of NRF2.…”
Section: Potential Role Of Pgam5 In Mitochondrial Biogenesismentioning
confidence: 99%
See 1 more Smart Citation